Combination early-phase trials of anticancer agents in children and adolescents - Moreno, Lucas; DuBois, Steven G.; Glade Bender, Julia; Mauguen, Audrey; Bird, Nick; Buenger, Vickie; Casanova, Michela; Doz, François; Fox, Elizabeth; Gore, Lia; Hawkins, Douglas S.; Izraeli, Shai; et al. (Journal of clinical oncology, 2023)
PURPOSE - - There is an increasing need to evaluate innovative drugs for childhood cancer using combination strategies. Strong biological rationale and clinical experience suggest that multiple agents will be more efficacious than monotherapy for most diseases and may overcome resistance mechanisms and increase synergy. The process to evaluate these combination trials needs to maximize efficiency and should be agreed by all stakeholders. - - METHODS - - After a review of existing combination trial methodologies, regulatory requirements, and current results, a consensus among stakeholders was achieved. - - RESULTS - - Combinations of anticancer therapies should be developed on the basis of mechanism of action and robust preclinical evaluation, and may include data from adult clinical trials. The general principle for combination early-phase studies is that, when possible, clinical trials should be dose- and schedule-confirmatory rather than dose-exploratory, and every effort should be made to optimize doses early. Efficient early-phase combination trials should be seamless, including dose confirmation and randomized expansion. Dose evaluation designs for combinations depend on the extent of previous knowledge. If not previously evaluated, limited evaluation of monotherapy should be included in the same clinical trial as the combination. Randomized evaluation of a new agent plus standard therapy versus standard therapy is the most effective approach to isolate the effect and toxicity of the novel agent. Platform trials may be valuable in the evaluation of combination studies. Patient advocates and regulators should be engaged with investigators early in a proposed clinical development pathway and trial design must consider regulatory requirements. - - CONCLUSION - - An optimized, agreed approach to the design and evaluation of early-phase pediatric combination trials will accelerate drug development and benefit all stakeholders, most importantly children and adolescents with cancer.